Financial Institutions' Responsibilities to Protect Customer Funds: An Islamic Economic Analysis of the Bank Jambi Case - Hidayat, Achmad; Daud, Daud; Devi, Erwina Kartika (Journal of Indonesian Islamic Studies, 2026)
This study aims to analyze the responsibility of financial institutions for protecting customer funds from an Islamic economic perspective, using Bank Jambi as a case study. The Bank Jambi case is relevant because, on February 22, 2026, a digital service system disruption occurred alongside customer reports of missing balances. The incident was followed by a forensic audit, reporting to the Jambi Regional Police, coordination with the Financial Services Authority (OJK) and Bank Indonesia, and a commitment to compensate affected customers. This research applies a descriptive qualitative method through a case-study approach and normative Islamic economic analysis. Data were obtained through literature review and documentation of public sources and Islamic economic literature. The findings indicate that, from an Islamic economic perspective, the responsibility of financial institutions does not stop at collecting and managing funds. It also includes the obligation to uphold trust (amanah), protect customer wealth, provide transparency, offer complaint mechanisms, and restore losses fairly. The handling of the Bank Jambi case shows institutional accountability through audit, legal reporting, and fund compensation. However, the Islamic economic perspective also requires stronger prevention, accountability, and systemic protection so that public trust can be maintained.